Tajdidunnikah Mualaf (Study Kasus di Desa Tanjunganom Kecamatan Kepil Kabupaten Wonosobo) - Rino Pambudi; Reni Nur Aniroh (STIKes Ibnu Sina Ajibarang, 2025)
This article aims to describe the tajdidunnikah for converts in Tanjunganom Village, Kepil District, Wonosobo Regency, where no previous researchers have discussed the theme. This article is a type of qualitative research, primary data through direct interviews with the perpetrators of tajdidunnikah and local community leaders. Secondary data from literature that is relevant to the research. The research instruments were in the form of observation and interviews, then analyzed inductively and descriptively. The findings show that (1) Tajdidunnikah for converts in Tanjunganom Village, Kepil District, Wonosobo Regency was carried out en masse according to Islam by local Kyai, without the involvement of the local Religious Affairs Office (KUA), because they still have Islamic and state marriage books. In this case, the KUA only married the converts, who when they married were already Buddhists. The background of the community who converted to Islam carrying out tajdidunnikah was solely for reasons of caution (ikhtiath) because they had apostatized within a period of 15 years. What they did was without any coercion from any party but was part of an awareness after they consulted with local religious figures. The Islamic legal view regarding this matter is permissible with the argument that tajdid nikah is an action as a step to create comfort of the heart and ihtiyath (caution) which is ordered in religion after someone leaves Islam. (2) From a positive legal perspective, Law No. 1 of 1974 article 26 paragraph 2 is a written law and is generally binding and enforced through the government. However, in this case it cannot be handled by the KUA as the implementing party for the marriage registrar appointed by the state because they still hold a valid marriage certificate. In other words, there is no legal umbrella that orders the issuance of a new marriage book for a Muslim who changes religion and returns to Islam.